Phosphites effect on late blight control and physiological parameters in Commercial potato (Solanum tuberosum L.) in Argentina - Cicore, Pablo L. (2011)
Phosphite (Phi) has been recommended to enhance plant resistance against Phytophthora ssp. The purpose of this study was to evaluate the effect of calcium phosphite (PhiCa) and potassium phosphite (PhiK) under field conditions, taking into account physiological parameters, performance and protection against late blight in the foliage of two potato cultivars, and comparing these results to controlled in vitro experiments. Experimental design was a split plot in randomized complete blocks with four replicates. The main plot comprised two potato cultivars (Kennebec and Spunta) and the sub-plots three late blight control treatments: control, PhiCa and PhiK. The interaction between cultivar and treatment on the area under disease progress curve (AUDPC) was determined. In Kennebec, the PhiK treatment showed a significantly lower AUDPC than control and PhiCa treatments. No differences were detected between treatments on Spunta? In the detached-leaf tests, there was a significant treatment effect. In both cultivars, PhiK application resulted in a significantly lower damage growth rate (DGR) compared to the control and PhiCa treatments, although there was less difference in Spunta. Treatments tested had no significant effect on yield. However, PhiK application tended to increase yields by 20.5 and 14.8% in relation to control and PhiCa treatments respectively. Under experiment conditions, Phi decreased disease severity and increased yields, with differences between cultivars and chemical compounds.